Prevalence of Anxiety, Depression, and Stress Among Medical Students at the University of Benghazi - O. El-najjar, Aisha; S. Mussa, Sajidah; F. Hamad , Fatima; F. Sultan, Shifaa (Libyan Journal of Public Health Practices, 2025)
Anxiety, depression, and stress are significant indicators of student's mental health issues, and experiencing these symptoms can have a serious impact on individuals' well-being. This study aimed to assess the prevalence of anxiety, depression, and stress among medical students at the University of Benghazi in Libya. A cross-sectional study was conducted, using a web-based DASS-21 scale for data collection. The study included a sample of 741 medical college students, with 73.1% identifying as female and 26.9% as male. The findings revealed that 58.2% of females reported extremely severe anxiety, followed by 41.3% for stress and 40.5% for depression. Among males, 17.4% reported extremely severe anxiety, 14.0% reported depression, and 12.8% reported stress. In terms of age groups, the 19–21-year-old group had the highest rates of depression at 8.4%, followed by 13.5% and 8.9% for anxiety and stress, respectively. The 22–24 years old group had the highest rates of depression at 29.7%, anxiety at 38.9%, and stress at 28.6%. The study revealed that anxiety was more prevalent than both depression and stress among students aged 25 and older. Furthermore, the study investigated the factors contributing to these psychological issues and identified academic pressure, exhaustion, and poor time management as the primary causes of mental problems among students.